MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF MATEMATIS SISWA MELALUI MODEL PEMBELAJARAN EXPERIENTIAL LEARNING - Lia Kurniawati; Kadir Kadir; Nefita Octafiani (Faculty of Educational sciences, UIN Syarif Hidayatullah Jakarta, 2019)
The purpose of this study was to analyze the effect of experiential learning learning models on students' mathematical creative thinking abilities. This research was conducted at MTsN Pagedangan 2014/2015 Academic Year. The research method is quasi-experimental, using a posttest only randomized control group design. The research sample consisted of 56 eighth grade students consisting of 26 experimental class students and 30 control class students obtained by cluster random sampling technique. Data collection on mathematical creative thinking abilities using test instruments. The results revealed that students 'mathematical creative thinking abilities taught with experiential learning models were higher than students' mathematical creative thinking abilities taught with conventional models (t obs = 3,573 and p-value = 0,0005 <0.05). The achievement of students' mathematical creative thinking abilities taught experiential learning models for fluency indicators was 71.15% and for elaboration 53.21% while students who were taught conventional learning on fluency indicators were 57.50% and elaboration 47.22%. The conclusion of this study, experiential learning learning model is more effective in increasing students' mathematical creative thinking abilities compared to conventional models.